The Relationship between Management Ability and Audit Fees by Considering Firm Credit and Auditor’s Dependency during Financial Crises - Iman Rasaei; Mahmoud Mousavi Shiri (Iranian Journal of Accounting, Auditing & Finance)
This paper aims to assess the relationship between management ability and audit fees by considering firm credit and auditor’s dependency during the financial crisis. Despite the presence of extensive studies on determining factors in audit fees, most of the studies have been concentrated on determining factors at the firm level, and little evidence is available to auditors on the information content of special managerial features. This paper aims to examine the relationship between managerial abilities and audit fees by considering firms' financial crisis conditions.In this paper, management abilities are considered to form three firm size indices, the firm's sales share in the market and cash. Moreover, the standard deviation of 3-year sales is used for firm credit, and an abnormal audit fee is employed for calculating auditor dependency. For this purpose, a total number of 91 listed firms on the Tehran Stock Exchange is evaluated for 6 years between 2014 and 2019. The panel regression model is used for hypothesis testing, and Chow and Hausman's tests are used for selecting the appropriate model-fitting method. The VIF test is used for analyzing linearity among explanatory variables. The obtained results indicate that financial crisis conditions contribute to the relationship between management abilities (based on firm size measurement) and audit fees. Further, the results indicate the negative impact of firm credit on the relationship between audit fee and management ability (based on cash). According to the results, audit fee dependency on the relationship between management ability (based on measurement, the firm's sales share, and cash) and audit fee is positive. Moreover, the results suggest that financial crisis conditions contribute to firm credit effectiveness in the relationship between management ability and audit fees.In past research, some factors affecting the auditor fee are debts, management ability, and auditor independence. In this paper, we contribute to the financial crisis as a variable that influences some of these relationships. And we show that relationships make sense by considering this variable.